Improving in vitro propagation of Protea cynaroides L. (King Protea) and the roles of starch and phenolic compounds in the rooting of cuttings - Reinhardt, Carl Frederick (Charlie) (University of Pretoria, 2013)
Thesis (PhD (Horticulture))--University of Pretoria, 2006.